2017
DOI: 10.1002/uog.15972
|View full text |Cite
|
Sign up to set email alerts
|

Preterm delivery after fetoscopic laser surgery for twin–twin transfusion syndrome: etiology and risk factors

Abstract: iPPROM and an increased number of ablated placental anastomoses were associated independently with SPT and IND preterm deliveries. A shorter preoperative cervical length was associated with SPT preterm delivery. Strategies to prevent iPPROM and for management of cervical length shortening are needed urgently in these pregnancies. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 26 publications
(31 reference statements)
4
27
1
5
Order By: Relevance
“…To further study this high-risk subset of patients, we propose a future study comparing serial qfFN levels in TTTS patients with and without a cerclage. In addition, the current study did not demonstrate preoperative cervical length to be a significant risk factor for preterm birth, However, prior larger studies have demonstrated preoperative cervical length to be an important predictor of preterm birth after laser surgery for TTTS 2,4,24 . For instance, thresholds such as a preoperative cervical length <20 mm 2 or <28 mm 24 have been associated with an increased risk spontaneous preterm birth after laser surgery.…”
Section: Discussioncontrasting
confidence: 87%
“…To further study this high-risk subset of patients, we propose a future study comparing serial qfFN levels in TTTS patients with and without a cerclage. In addition, the current study did not demonstrate preoperative cervical length to be a significant risk factor for preterm birth, However, prior larger studies have demonstrated preoperative cervical length to be an important predictor of preterm birth after laser surgery for TTTS 2,4,24 . For instance, thresholds such as a preoperative cervical length <20 mm 2 or <28 mm 24 have been associated with an increased risk spontaneous preterm birth after laser surgery.…”
Section: Discussioncontrasting
confidence: 87%
“…Two hundred and thirty studies were therefore deemed eligible after full‐text review. From these, all randomized trials ( n = 6) and the largest observational studies ( n = 94) were selected for analysis (Figure ). There were 13 case–control studies, 32 prospective cohort studies and 49 retrospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…The fact that TTTS infants are still born prematurely is mostly due to PPROM after laser surgery. Iatrogenic PPROM occurs in up to 30% of cases [50,51]. Maternal complications of laser surgery are also not consistently reported, but appear to occur in about 5% of cases and include abdominal pain after leakage of amniotic fluid into the peritoneal cavity, chorioamnionitis, bleeding, pulmonary edema and placental abruption [45].…”
Section: Complications Of Fetoscopic Laser Surgerymentioning
confidence: 99%